2015
DOI: 10.1371/journal.pone.0139141
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mechanism of Hyperglycemia-Induced Fetal Cardiac Hypertrophy

Abstract: Hyperglycemia in diabetic mothers enhances the risk of fetal cardiac hypertrophy during gestation. However, the mechanism of high-glucose-induced cardiac hypertrophy is not largely understood. In this study, we first demonstrated that the incidence rate of cardiac hypertrophy dramatically increased in fetuses of diabetic mothers using color ultrasound examination. In addition, human fetal cardiac hypertrophy was successfully mimicked in a streptozotocin (STZ)-induced diabetes mouse model, in which mouse cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…To determine whether diabetes mellitus altered the cardiac morphology, the hearts were harvested at the end of the study. These hearts were photographed and fixed in 4% para-formaldehyde [23] . Then, tissues were dehydrated, embedded in paraffin blocks, cut into 5-μm sections, and mounted on 3-aminopropyltriethoxysilane-coated slides.…”
Section: Hematoxylin and Eosin (Hande) Stainingmentioning
confidence: 99%
“…To determine whether diabetes mellitus altered the cardiac morphology, the hearts were harvested at the end of the study. These hearts were photographed and fixed in 4% para-formaldehyde [23] . Then, tissues were dehydrated, embedded in paraffin blocks, cut into 5-μm sections, and mounted on 3-aminopropyltriethoxysilane-coated slides.…”
Section: Hematoxylin and Eosin (Hande) Stainingmentioning
confidence: 99%
“…Previous studies have shown that mitochondrial ROS activates multiple pathways related to cellular damage in the setting of hyperglycemia [8891]. An increase in 3-nitrotyrosine in association with increased cell death has been noted in human myocardial samples [15, 92], as well as in a streptozotocin (STZ)-induced model of Type 1 diabetes [93]. Indeed, Cai et al demonstrated a reduction in nitrosative damage with overexpression of metallothionein, an antioxidant protein, in STZ-treated mice [94].…”
Section: Mechanism Of Mitochondrial Dysfunction In Diabetic Heartmentioning
confidence: 99%
“…In animal studies it was found that the cardiac changes are ascribed to cardiomyocyte hypertrophy and the suppression of cardiac transcription factors in both ventricular walls, as well as the ventricular septum, and are not driven by cell proliferation or apoptosis. 16 Patients with known pre-gestational target-organ damage, especially nephropathy, are at particular risk of intra-uterine growth restriction; 17 however, none of the five mothers with small-forgestational-age babies had nephropathy.…”
mentioning
confidence: 99%